(untitled) (International Journal of Physiotherapy, 2017)
Background: Swiss ball is used as a tool in stroke rehabilitation It is commonly used to improve postural control. Sitting on unstable surfaces can provoke lower extremity muscle contractions as a component of postural control. Effect of unstable surface sitting on lower extremity control and functions following stroke is not clear from available literature. Hence this study was planned to study the effect of Swiss ball training on sit to stand function, weight bearing through paretic lower limb and motor control of paretic limb in patients with hemiplegia. Methods: First-time stroke patients with hemiplegia were recruited from an acute stroke care set up in a University teaching hospital and assigned to control (n=34) and experimental group (n = 33). Along with physiotherapy based on impairments, patients in control group were trained for sitting to standing and sitting activities on a stool, and from in the experimental group were trained with Swiss Ball. Both the groups underwent 40 minutes of training for ten days. 30-second sit to stand, Percentage of weight bearing through the paretic limb and Brunnstrom stages were recorded. Parametric and non-parametric tests were used based on the outcome tested. Results: The baseline characteristics between the groups were similar statistically. Post-intervention experimental group had better weight bearing ability and motor control of lower limb (p<0.05), than the control group. The difference in 30-second sit to stand did not reach statistical significance (p=0.059). Conclusion: Training with Swiss ball results in greater improvement in weight - bearing ability and motor control of paretic lower limb, compared to conventional training. The Swiss ball training does not enhance the sit to stand performance more than conventional training.